(untitled) (American Journal of Islam and Society, 2014)
The significance of the epistles on a range of intellectual disciplines by the group of scholars known as the Brethren of Purity (Ikhwan al-Safa’) has been known for some time, although one might argue that their significance for a proper assessment of Islamic intellectual history has been neglected. The 116 The American Journal of Islamic Social Sciences 31:1 book under review is part of an exciting new project initiated by the Institute of Ismaili Studies in London to re-edit the whole text with critical analytical translations and annotations undertaken by a number of specialists around the world. For those of us who specialize in Islamic intellectual history and need texts to use in the classroom, this is an excellent and most welcome development. The companion volume edited by el-Bizri, which attempts not only to make sense of who the Ikhwan were but also to assess their impact, demonstrates that their significance was recognized by later traditions even when it was occluded. One small quibble – it would have been good to see the Arabic and English on facing pages, which may have been logistically problematic. As it is, it makes the comparison of the original text with the English a bit more difficult. The two epistles translated here are the first in the sequence and constitute part of the first section of the Rasā’il on the mathematical and propaedeutical sciences (al-‘ulūm al-riyādīyah al-ta‘līmīyah). Nader el-Bizri, the translator and editor of the series, is a historian of philosophy and science in the Islamic world and has recently been focusing on the history of geometry, mathematics, and optics and publishing widely on Ibn al-Haytham (d. 1040). These two epistles form part of the ancient quadrivium that constituted a more advanced stage of study associated with Boethius (d. 524) and was based upon the mathematics of Nicomachus of Gerasa, a Neopythagorean of the first century CE: training in arithmetic, geometry, music, and astronomy were considered to be the very heart of a scientific education. After the first two epistles, epistle 3 deals with astronomy, epistle 4 with cosmography, epistle 5 with music, and epistle 6 with proportions (that ties the quadrivium together) – and that is before they move onto the next set of propaeduetics, namely the logical organon beginning with epistles 7 and 8 (the theoretical and practical arts) that provide a classification of the sciences on which the approach to holism is based ...